Are Marine Accident Really Accident? Fallacy of Random Marine Accidents in Dry Cargo Fleet - Bulut, Emrah; Yoshida, Shigeru (ELSEVIER SCIENCE BV, 2015)
The aim of this paper is to investigate the relation between marine casualty and dry bulk cargo freight rate according to the existence of spurious accident phenomenon in the dry cargo vessel accidents. According to the conventional expectation, the volume of marine accidents is a random process since it is accidently occurred and not a man- made outcome. Under this circumstance, it is expected that the volume of marine accidents should be statistically uncorrelated with the freight market rates and positively correlated with the fleet size. However, the existence statistics on dry cargo marine accidents indicate high level of negative correlation with freight markets (- 0.95 for no. of vessels and - 0.79 for the volume of accidents in dwt) and also high level of negative correlation with the fleet size (- 0.81 for the volume of accidents in dwt). The asymmetric interaction between the widely accepted facts and the statistical foundations is the main concern of this paper which is named the Fallacy of Random Marine Accidents (FRMA). The possible reasons of the FRMA phenomenon are considered to be based on the man- made marine accidents because of the financial collapse or as the well known term the credit default risk.
Keywords: Marine Accident Fallacy; Freight Market; Causality Analysis; Dry Cargo Shipping; Transportation